Non-genetic effects on productive traits of hair lambs housed in raised slatted floor cage in the sub-humid tropics of Mexico - Estrada-León, Raciel Javier (2023)
This study aimed to determine the effects of space allowed (SA), season of the year (SY) and year (YR), and simple interactions on productive traits of hair lambs housed in raised slatted floor cage (RFC). Data from initial weight (IW, kg), final weight (FW, kg), adjusted weight at 90 days (FWA, kg), daily weight gain (DWG, g) and finalization period (FP) of 982 lambs were evaluated. Data for FW, FWA and DWG was analysed using general linear models and FP using survival analysis. The model included fixed effects of SA (0.47-0.53, 0.56-0.60, 0.64-1.13 m2/animal), SY (dry, rainy, north) and year (2012, 2013), the simple interactions and IW as a covariate. Mean IW, FW, FWA, DWG were 14.29±3.52, 35.75±3.11, 40.50±5.91 kg, and 286± 50 g, respectively, with 72.15± 14.45 of FP. The SA affected FW, FWA and DWG, SY affected only FW and YR affected significantly all the study variables. Lambs in spaces of 0.47-0.53 m2 have a higher probability or risk (1.986) to extend the FP. In conclusion, SA, SY, and YR had effect on the productive traits of hair lambs housed in RFC; lambs with larger SA were more productive in a shorter finalization period than those with smaller SA.